1997
DOI: 10.1128/jvi.71.5.3992-3997.1997
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, purification, and characterization of the human coronavirus 229E 3C-like proteinase

Abstract: Coronavirus gene expression involves proteolytic processing of the gene 1-encoded polyprotein(s), and a key enzyme in this process is the viral 3C-like proteinase. In this report, we describe the biosynthesis of the human coronavirus 229E 3C-like proteinase in Escherichia coli and the enzymatic properties, inhibitor profile, and substrate specificity of the purified protein. Furthermore, we have introduced single amino acid substitutions and carboxyl-terminal deletions into the recombinant protein and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 35 publications
8
128
3
Order By: Relevance
“…For optimization of this cleavage assay, nsp4His was preferred over MBP-nsp4 because the purification of the latter was a more elaborate process. Although it was reported that the addition of six His residues strongly inhibited the enzymatic activity of the human coronavirus 229E 3CL pro proteinase (Ziebuhr et al, 1997), in both our assays the catalytic activity of nsp4His was very comparable to that of partially purified uncleaved or cleaved MBP-nsp4. Also, the in vivo trans-cleavage activity of nsp4His, as determined using the recombinant vaccinia virus/T7 expression system (data not shown), was comparable to that of untagged nsp4, suggesting that the presence of the (His) 6 tag did not affect nsp4 proteolytic activity.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…For optimization of this cleavage assay, nsp4His was preferred over MBP-nsp4 because the purification of the latter was a more elaborate process. Although it was reported that the addition of six His residues strongly inhibited the enzymatic activity of the human coronavirus 229E 3CL pro proteinase (Ziebuhr et al, 1997), in both our assays the catalytic activity of nsp4His was very comparable to that of partially purified uncleaved or cleaved MBP-nsp4. Also, the in vivo trans-cleavage activity of nsp4His, as determined using the recombinant vaccinia virus/T7 expression system (data not shown), was comparable to that of untagged nsp4, suggesting that the presence of the (His) 6 tag did not affect nsp4 proteolytic activity.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the purified EAV nsp4His proteinase showed catalytic activity on all peptides, its activity was very weak compared to that of other 3C-like proteinases in similar experiments (Cordingley et al, 1989;Hammerle et al, 1991;Hegyi et al, 2002;Jewell et al, 1992;Ziebuhr et al, 1997). Therefore, to investigate whether a differently purified nsp4 proteinase might perform better, the catalytic activity of nsp4His proteinase was compared to that of a partially purified MBP-nsp4 proteinase.…”
Section: Nsp4 Cleavage Assay With Synthetic Peptide Substratesmentioning
confidence: 93%
See 1 more Smart Citation
“…The 3CL pro s of the four main nidovirus branches are profoundly diverged and (according to conventional criteria) do not group together, although they have become significantly separated from their viral and cellular homologs. Even the catalytic center, which is uniformly conserved in cellular homologs, has evolved into quite different forms, including a Cys-His catalytic dyad in roni-and coronaviruses, a Ser-His-Asp catalytic triad in arteriviruses, and a Ser-His-based catalytic center in toroviruses (Anand et al, 2002Barrette-Ng et al, 2002;Draker et al, 2006;Ziebuhr et al, 1997Ziebuhr et al, , 2003. The crystal structures of coronavirus and arterivirus 3CL pro s revealed that both groups of enzymes have a three-domain structure, with domains I and II forming a (chymotrypsin-like) two-ß-barrel fold consisting of 12 or 13 ß-strands (Anand et al, 2002Barrette-Ng et al, 2002;Yang et al, 2003).…”
Section: Replicase Machinery: the Conserved Nidovirus Backbonementioning
confidence: 99%
“…These studies allowed us to identify the active-site amino acid residues with a combination of site-directed mutagenesis studies (Boniotti et al, 1994;Cheah et al, 1990;Gosert et al, 1997;Hammerle et al, 1991). Several 3C and 3C-like proteases were purified and their biochemical properties were well characterized (Baum et al, 1991;Chisholm et al, 2001;Davis et al, 1997;Ziebuhr et al, 1997). They are characterized by their proteolytic activities being inhibited by both cysteine and serine protease inhibitors.…”
Section: Introductionmentioning
confidence: 99%